Rethinking Reactivity: How Structure, Energy, and Entropy Drive Chemical Transformations - Alzeer, Jawad (Jurnal Pijar Mipa, 2025)
This work introduces a new way to understand chemical and biological reactivity by connecting molecular structure directly to potential energy and entropy. Moving beyond traditional views, where potential energy is merely “stored energy” and entropy a measure of “disorder”, this structural-thermodynamic framework defines both properties through the lens of constitution, configuration, and conformation. By analyzing diverse mechanisms, including nucleophilic substitutions, eliminations, and cycloadditions, the study shows how structure drives energy storage and release, as well as entropic expansion. The framework highlights how organization increases potential energy while dissociation and flexibility enhance entropy. This structural view not only clarifies the thermodynamic basis of reaction pathways but also offers a predictive model for molecular design in drug development, catalysis, and computational chemistry. By linking structure to thermodynamic behavior, the approach helps students and researchers move from memorization to mechanistic reasoning, providing a unified tool to interpret and anticipate chemical transformations.